2012
DOI: 10.1177/0961203312468625
|View full text |Cite
|
Sign up to set email alerts
|

Extent and characteristics of self-reported pain in patients with systemic lupus erythematosus

Abstract: These findings expand the current knowledge of the extent of SLE-related pain and how patients perceive this pain. The results can contribute to affirmative, supportive and caring communication and especially highlight SLE-related pain in patients with a short disease duration and high disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 81 publications
(171 reference statements)
4
23
0
Order By: Relevance
“…Firstly, joint pain is frequently reported by patients as one of the most common and disabling clinical manifestations [11]. Interestingly, in a study published in 2008, Malcus Johnsson et al have shown the presence of hand problems interfering with daily activities in 73% of SLE patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, joint pain is frequently reported by patients as one of the most common and disabling clinical manifestations [11]. Interestingly, in a study published in 2008, Malcus Johnsson et al have shown the presence of hand problems interfering with daily activities in 73% of SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…While for decades joint involvement in SLE has been considered mild and nonerosive, many studies have recently showed that patients with SLE develop joint deformities and, in up to 10% of the cases, an erosive deforming arthritis [7][8][9]. In addition, from the patient's perspective, joint pain is one of the most commonly reported symptoms that impact on quality of life [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Pain has also been reported to be a symptom which health professionals do not pay sufficient attention to [ 13 15 ]. Although pain is a commonly reported symptom in SLE, there is a large variation between different patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that nearly one quarter of a cohort with patients with SLE reported a high degree of pain on a visual analogue scale (VAS) ≥ 40 mm, and these patients also reported more fatigue, reduced health-related quality of life, and more signs of anxiety and depression [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…They represent the heralding symptom in 60-80% of cases and are reported in up to 60% of disease flares (3,4). Inflammatory MS manifestations are described as a major cause of pain and compromised hand function, interfering with daily activities in 73% of SLE patients and causing low productivity or work disability in 49% and 17% of them, respectively (5)(6)(7)(8). In particular, impairment of patients' health related quality of life (HRQoL) is mostly associated with MS flares (9,10).…”
Section: Introductionmentioning
confidence: 99%